Performance of Arbuscular Mycorrhiza Inoculated Acacia mangium Seedlings on Degraded Land with Different Rates of Phosphorus - Satter, M Abdus; Hanafi, M Musa; Mahmud, Tenku MM; Azizah, Hashim (Bangladesh Journal of Microbiology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> The experiment was conducted in the degraded ex-tin mining farm of Universiti Putra Malaysia during November 1998 to May 1999. The experiment was laid out in split plot design with three replications. Three phosphorus (P) rates, viz., 0, 50 and 100 g Gaphsa phosphate rock (GPR) per plant in combination with and without arbuscular mycorrhiza (AM) inoculation were studied on newly planted tree species Acacia mangium. Mycorrhiza inoculation was assigned to the main plot and P dose to the subplot. Three-month-old AM preinoculated seedlings were planted in the field at 2 m x 2 m spacing. The experiment was continued until 160 days after planting (DAP). Mycorrhiza inoculation and rate of P application significantly influenced growth and development of the A. mangium plants. The highest growth of un-inoculated A. mangium plants was observed with 100 g GPR per plant; whereas for AM inoculated plants the highest growth was observed with 50 g GPR per plant. This indicates that P requirement of newly planted A. mangium plants on degraded ex-tin mining land could be reduced to 50 g GPR per plant, i.e., by 50% with AM inoculation. Keywords: Arbuscular mycorrhiza, Acacia mangium, Degraded land, Phosphorus DOI: http://dx.doi.org/10.3329/bjm.v24i1.1230 Bangladesh J Microbiol, Volume 24, Number 1, June 2007, pp 9-18